Análise da dinâmica hidrogeomorfológica do canal do alto curso do Rio Paraíba - Gomes, Fábio Vitorino (2024)
Water scarcity is one of the most important indicators for humanity. Remaining constant attention to this issue is of crucial importance, as this scarcity is one of the barriers to social development. One of the ways to combat water deficit is through the introduction of river flow from generally perennial channels, where this process takes place within the same river basin or another basin. This dynamic of water transfer by rivers is called transposition. The present work aims to deepen the discussion on hydrogeomorphological dynamics in semi-arid river environments, more specifically in the Upper Course basin of the Paraíba River where there is a predominance of intermittent and ephemeral rivers. The methodology focused on the hydrological analysis of evolution and flow in which the reflection of these variables before the start of operations of the PISF (São Francisco River Integration Project) proved to be positive and subsequent start of operations was negative. The analysis of the monitored sections provided by the images generated by the UAV (Unmanned Aerial Vehicle) shows changes in the geomorphic units found in the channel, corroborating the prediction of geomorphological changes caused by the introduction of the river flow generated by the PISF.